Hypolipidemic Effects of Alkaloids from Rhizoma Coptidis in Diet-Induced Hyperlipidemic Hamsters - He, Kai; Kou, Shuming; Zou, Zongyao; Hu, Yinran; Feng, Min; Han, Bing; Li, Xuegang; Ye, Xiaoli (Planta Medica, 2016)
This study was conducted to evaluate the antihyperlipidemic activity of five major alkaloids in Rhizoma Coptidis using high-fat- and high-cholesterol-induced hyperlipidemic hamsters. Hyperlipidemic hamsters were treated with coptisine, berberine, jatrorrhizine, palmatine, epiberberine, and total Rhizoma Coptidis alkaloids with a dose of 46.7 mg/kg × day for 140 days. Serum total cholesterol, triglyceride, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and total bile acids were examined after alkaloid treatment. The results showed that all therapy agents prevented body weight gain, reduced the serum total cholesterol, and increased the high-density lipoprotein cholesterol of hamsters. Berberine, jatrorrhizine, and total Rhizoma Coptidis alkaloids decreased the triglyceride level in hyperlipidemic hamsters, while coptisine, jatrorrhizine, palmatine, and total Rhizoma Coptidis alkaloids significantly suppressed the elevation of the low-density lipoprotein cholesterol level. The fecal excretion of bile acids was significantly elevated by berberine, coptisine, jatrorrhizine, palmatine, total Rhizoma Coptidis alkaloids, and orlistat. Notably, total Rhizoma Coptidis alkaloids possess a much stronger lipid-lowering effect than the pure Rhizoma Coptidis alkaloids. Quantitative reverse transcription-polymerase chain reaction analyses revealed that Rhizoma Coptidis alkaloids could retard the synthesis of cholesterol by downregulating the mRNA expression of 3-hydroxy-3-methyl glutaryl coenzyme A reductase and accelerate the clearance of lipids by upregulating the low-density lipoprotein receptor, cholesterol 7α-hydroxylase, and uncoupling protein-2 expression. These findings highlight the critical role of Rhizoma Coptidis alkaloids in hyperlipidemia treatment. Thus, they need to be considered in future therapeutic approaches.
Keywords: Rhizoma Coptidis; Ranunculaceae; alkaloids; hyperlipidemic hamsters; antihyperlipidemic; mechanism